Research on the Fire Hazards of Cells in Electric Car Batteries - Oleksandr Lazarenko (Bezpieczeństwo i Technika Pożarnicza, 2018)
Aim: To carry out an analysis of the latest research in the field of fire hazard lithium-ion cells, which are used in accumulator batteries of electric cars. Proceeding from the obtained results of the research, to determine the direction of the subsequent research in the field of fire safety of lithium-ion ac-cumulator batteries of electric cars. Methods: This work is based on the fundamental research of scientists from the US, China and other countries of the world, the results of which were presented in a variety of world scientific journals, conferences and national reports. Results: An analysis of literature sources has shown that research in the field of fire safety of lithium-ion batteries is carried out all around the world, as this technical device is constantly being modified and improved, as dictated by today's realities. The obtained research results show that the elementary lithium-ion cell contributes during combustion to the production of 6 to 10 kW of energy and a rather large number of dangerous combustion products, especially HF, POF3. Also, the results of the studies show unambiguously that the amount of energy released by lithium-ion cells supply as well as the amount of hazardous combustion products will depend on the degree of their charge. Fur-thermore, the shown research results unequivocally confirm that the amount of energy released by the lithium-ion battery depends on the degree of its charge. Based on the results of full-scale experiments, the average amount of water necessary to extinguish the battery of an electric car varies from 2500 to 6000 litres, which can exceed the amount of water carried by a single fire truck. The amount of thermal radiation at a distance of 1.5 meters from the model of a burning car with decor elements, is between 8.1 and 11.9 kW/m2. Labora-tory analysis of samples of water, used to extinguish a car, showed the presence of hydrogen chloride (HCl) and hydrogen fluoride (HF) in concentrations 2–3 times higher and more than 100 times higher, than normal registered levels, respectively. No other corrosive or toxic compounds were found in the water samples. Conclusions: Subsequent work to investigate the fire safety of electric car accumulators and their supply elements can be devoted to conducting full-scale experiments on the extinguishing of real consumer electric cars. Followed by an assessment of the problems of access to batteries and the difficulty of their extinguishing, the risk of electric shock from the battery of an electric car and the possibility of using various extinguishing media should be explored. It is also very urgent to develop a mathematical model for the heating of a lithium-ion battery that takes into account the geometric shape of the element and its chemical composition.